1. \( 6 x+7=7 x+13 \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the equation \( 6x + 7 = 7x + 13 \), start by isolating the variable \( x \). Subtract \( 6x \) from both sides to get \( 7 = x + 13 \). Next, subtract \( 13 \) from both sides to find \( x = 7 - 13 \), which simplifies to \( x = -6 \). Now, let's plug \( x = -6 \) back into the original equation to verify our solution. If both sides equal, then we know we have the right answer. Try it out and confirm you’ve cracked the equation! If you ever find yourself tangled up with algebra, remember: keeping both sides of the equation balanced is key. And don’t hesitate to double-check! Many students rush through calculations, which can lead to pesky mistakes. Slow down, and always aim for clarity!